Histology and ultramorphology of the mesenteric sacs in the Neotropical termite Neocapritermes opacus (Blattaria, Termitidae, Termitinae) - da Silva, Iago Bueno [UNESP]; Buganeme, Sandra Daruiche [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Elsevier, 2020)
Neocapritermes opacus is a Neotropical termite, which feeds on a variety of food sources, including highly decayed wood and humus. Similar to many Termitidae, this species contains a mixed segment in the intestine, an anatomic distinct region composed of both mesenteric and proctodeal tissues. In Neocapritermes spp., a pair of intestinal protrusions referred to as mesenteric sacs are associated with the mixed segment. In the present study, with the aid of histological and scanning microscopy techniques, we provide a detailed anatomical and histological analyses of the mesenteric sacs in N. opacus workers. The results showed that the paired sacs are contiguous with the mesenteric component of the mixed segment and open into the ectoperitrophic space. The wall of the sacs is an epithelium composed of two types of cells (regenerative and principal) and musculature. The regenerative cells are located at the epithelium base and organized in regenerative crypts, while the principal cells are columnar and enfold the lumen of the sacs. Brush border was observed in the principal cell apex, aligned closely to rod-like bacteria. Secretory activity was observed in the principal cells and vesicles cast from them toward the sacs lumen, probably result of an apocrine activity. The sac epithelium was of mesenteric affiliation but differed from the intestinal midgut. The proctodeal epithelium was markedly different. Although some studies have been interpreted the mesenteric sacs as Malpighian nodules or Malpighian sacs, our results support that these structures are morphologically distinct and that the occurrence of mesenteric sacs is a synapomorphy for Neocapritermes. The precise function of the mesenteric sacs in termite digestion remains unclear; therefore, further investigations should carefully consider their secretory activity and symbiont population, aiming to understand their development and maintenance among these Neotropical species.
Keywords: Digestive system; Mixed segment; Scanning microscopy; Secretory activity; Synapomorphy; Termites